Enhancing global‐scale urban land cover representation using local climate zones in the Community Earth System Model - Yuan Sun (17888210) (2025)
This dataset contains single-point simulation scripts, inputs, and outputs, as the supplementary informaton for the pubkication "Enhancing Global‐Scale Urban Land Cover Representation Using Local Climate Zones in the Community Earth System Model", doi: https://doi.org/10.1029/2025MS004934 Abstract Urban areas are increasingly vulnerable to the impacts of climate change, necessitating accurate simulations of urban climates in Earth system models (ESMs) in support of large-scale urban climate adaptation efforts. ESMs underrepresent urban areas due to their small spatial extent and the lack of detailed urban landscape data. To enhance the accuracy of urban representation, this study integrated the local climate zones (LCZs) scheme within the Community Earth System Model (CESM) to better represent urban heterogeneity. We adopted a modular approach to incorporate the 10 built LCZ classes into CESM as a new option in addition to the default urban three-class scheme (i.e., tall building district, high density, and medium density). CESM simulations using the LCZ-based urban characteristics were validated globally at 20 flux tower sites, showing site-averaged improvement in modeling upward longwave radiation (LWup) and anthropogenic heat flux (Qahf), but increased uncertainties in modeling sensible heat flux (Qh). The root-mean-square error between the observed and simulatedusing the LCZ decreased by 4% compared to using the default. Model sensitivity experiments revealed that LWup and Qh had comparable sensitivity to LCZ urban morphological and thermal parameter subsets. This study assessed and demonstrated the implementation as the starting point for future work on better resolving urban areas in Earth system modeling.